Biallelic KITLG variants lead to a distinct spectrum of hypomelanosis and sensorineural hearing loss. (25th May 2022) - Vona, B.; Schwartzbaum, D.A.; Rodriguez, A.A.; Lewis, S.S.; Toosi, M.B.; Radhakrishnan, P.; Bozan, N.; Akın, R.; Doosti, M.; Manju, R.; Duman, D.; Sineni, C.J.; et al.
Abstract: Background: Pathogenic variants in KITLG, a crucial protein involved in pigmentation and neural crest cell migration, cause non‐syndromic hearing loss, Waardenburg syndrome type 2, familial progressive hyperpigmentation and familial progressive hyper‐ and hypopigmentation, all of which are inherited in an autosomal dominant manner. Objectives: To describe the genotypic and clinical spectrum of biallelic KITLG ‐variants. Methods: We used a genotype‐first approach through the GeneMatcher data sharing platform to collect individuals with biallelic KITLG variants and reviewed the literature for overlapping reports. Results: We describe the first case series with biallelic KITLG variants; we expand the known hypomelanosis spectrum to include a 'sock‐and‐glove‐like', symmetric distribution, progressive repigmentation and generalized hypomelanosis. We speculate that KITLG biallelic loss‐of‐function variants cause generalized hypomelanosis, whilst variants with residual function lead to a variable auditory‐pigmentary disorder mostly reminiscent of Waardenburg syndrome type 2 or piebaldism. Conclusions: We provide consolidating evidence that biallelic KITLG variants cause a distinct auditory‐pigmentary disorder. We evidence a significant clinical variability, similar to the one previously observed in KIT ‐related piebaldism.